Direct Extraction and Conversion of Microalgal Lipid from Chlorella vulgaris to Biodiesel Through In Situ Process Assisted by Sonication - Wulandari, Melysa; Hadi, Sofijan; Purkan, Purkan; Sumarsih, Sri; Abdulloh, Abdulloh; Wahyuni, Dwi Kusuma; Piluharto, Bambang (Molekul, 2024)
Direct extraction and conversion of microalgal lipid to biodiesel in one step process is developed to initiate an efficiently method in the biofuel production. The method that called as in-situ process had been applied in the biodiesel production from microalgae Chlorella vulgaris lipid by involving of sonication assisting. Various parameters that affect the in-situ transesterification were investigated to find the optimum conditions including power of sonication, co-solvent use, and biomass amount. The experiment was performed by acidic catalyst The use of sonication in 25kHz/270W yielded the highest biodiesel product. The apply of co-solvent n-hexane significantly increased the yield biodiesel rather than no co-solvent. The biodiesel yield of 10.39 % obtained when the process was accompanied by the n-hexane.as co-solvent with increasing level as 47% rather than without co-solvent. The in situ process in the ratio biomass - methanol 3:50 that assisted by sonication for 60 mins produced the highest biodiesel, which was 20,31 % w/w. The yield was higher than assisting with reflux or combination of reflux-sonication. The component of biodiesel yielded in the process consisting of 7,10,13-hexadecatrienoic methyl ester; pentadecanoic acid, 14-methyl-methyl ester; 9,12,15-octadecatrienoic acid-methyl ester; and eicosanoic acid-methyl ester. Joining of reflux-sonication exhibited a low biodiesel product. Disadvantage method from the combination may inhibit on lipid extraction or FAME transformation, the exact cause needs to be looked for in the future. Keywords : Biodiesel, in-situ transesterification, microalgae Chlorella vulgaris, sonication